Perspective of sustainable Piemontese cattle rearing in the north-west of Italy - Lazzaroni C.; Biagini D. (Mediterranean livestock production: uncertainties and opportunities, 2008)
To verify the prospects of sustainable livestock development of Piemontese cattle in their distribution areas, a survey was conducted with local farmers. Despite the reduction in the number of animals, the Piemontese breed is reared in extensive and traditional systems, as well as in marginal areas, because of the revenues farmers can obtain from the typical and high quality products. In the mentioned areas animals are normally fed on pasture and some producers complain about soil fertility losses due to the breed frugality that influences the amount of excreta, even if the breed hardiness confers animals a high adaptability to poor environments. In conclusion, Piemontese cattle rearing in the breed distribution areas is important to promote the territory and landscape maintenance and to avoid environmental imbalances. Political and financial measures recognising the additional market functions of such livestock systems could stimulate the local economy.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)